New Perspectives on the Early Slavs and the Rise of Slavic - Klír, Tomáš,Boček, Vít,Jansens, Nicolas (Universitätsverlag Winter, 2021)
The volume is addressed to one of the most fascinating issues in contemporary historical linguistics and medieval studies, which is the extremely fast expansion of the Slavic language across great parts of Europe in the Early Middle Ages. Traditionalists explain the spread of proto-Slavic as a result of migrations in the 6th–7th century and associate that with a specific material culture and with early mentions of ethnic Slavs in written sources. Alternative hypotheses attribute the same evidence to linguistically and genetically quite varied communities and associate the later spread of proto-Slavic with its status as a ‘lingua franca’ or ‘koiné’. The papers in the present volume interpret new methodological and empirical findings from several fields of study, not only from the traditional triad of linguistics, archaeology, and historiography, but also from adjacent disciplines such as religious studies, cultural anthropology, archaeogenetics, and others. The unifying thread is that the question of the relations between Slavic language, ethnicity, and material culture has differing answers in different geographical and political contexts.
9783825377519
Keywords: Geschichte; Sozial- und Kulturanthropologie; Ethnographie; Archäologie einer Periode / Region; Europa; Slavische Sprachen; ca. 500 bis ca. 1000 n. Chr.; 1000 bis 1500 nach Christus; Sprachgeschichte; Historische Sprachwissenschaft; Linguistik; Materielle Kultur; Mediävistik; slavische Sprachen; Proto-Slavisch; Völkerwanderung; Archäologie; Kulturanthropologie; Flußnamen; Indo-Europeanization; Soziolinguistik; Sprachvergleich; Keltisch; Sprachwandel; Ethnizität; Karolingerreich; Religionswissenschaft; Finno-ugrisch; Siedlungsgeschichte